Comparing growth and physiological responses of Globba schomburgkii Hook. f. and Globba marantina L. under hydroponic and soil conditions - Phantong, Piyamart; Machikowa, Thitiporn; Saensouk, Piyaporn; Muangsan, Nooduan (Emirates Journal of Food and Agriculture, 2018)
Globba (Zingiberaceae) are attractive herbaceous plants widely used as ornamental plants. However, cultivation is limited because of low propagation rate and depends on the season only. This research aimed to compare growth and physiological responses of Globba schomburgkii Hook. f. and Globba marantina L. under both soil and hydroponic conditions. In vitro plantlets (8 cm in height) were transplanted to a hydroponic culture with the nutrient film technique (NFT). In soil culture, the plantlets were transplanted to small pots containing sand: burned rice husk: peat moss (1:1:1 by volume). Vegetative growth characteristics were measured at 15, 30, 45 and 60 days after transplanting (DAT), whereas reproductive growth and physiological characteristics were measured at 60 DAT. All there was 100% survival in both growth conditions. Plants of both species grown in hydroponic conditions had higher shoot length, leaf area and stem diameter, except number of shoots than when propagated in soil conditions. Moreover, both species grown in hydroponics had earlier inflorescences and more flowers, indicating that they can be flowering out of season. Additionally, in hydroponic conditions both species had significant higher stomatal conductivity, whereas there were no significant differences in photosynthetic rates, transpiration rates and leaf temperature when compared with soil conditions. Therefore, our study provides evidence that G. schomburgkii and G. marantina are capable of adapting to hydroponic conditions and that hydroponics may be a suitable method for propagating Globba and other ginger plant species into cut flower or potted plants all year round.